KEADILAN DAN KEBENARAN PERSPEKTIF AKUNTANSI SYARIAH - Fahrudin A, SE., MM.,, Ahmad (IQTISHODUNA, 2007)
Accounting with Islamic values based on the justice and truth that is in line with al-Qur’an and al-Hadist is a reality that should be achieved because Islamic networking in Syariah is not merely summarizing God’s will. It is because the first Syariah source is God’s words (al-Qur’an). This ‘Tauhid’ belief is alive in Syariah and in an Islamic community. It is known that ‘Tauhid’ does not separate between social and spiritual lives. Accounting formula based on the justice and truth must reflect some items below: First, all of the corporation and organization elements had by the Moslems must reflect ‘zakat’; Second, Syariah Accounting must be characterized by ‘zakat’ and ‘amanah oriented’; Third, the accounting report design must cover some elements as cash-flow statement, current value balance sheet, and shariate value added statement (SVAS)